A Systematic Literature Review of School Literacy Movement Evaluations Using the CIPP Model in Elementary School - Novi Putriani Sukamto; Tri Murwaningsih; Chumdori Chumdori (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
This systematic literature review aims to synthesize empirical studies evaluating literacy programs in Indonesian Elementary Schools using the CIPP model. Literacy is a crucial foundation for human development and social progress. Following PRISMA guidelines, 12 studies published between 2015 and 2024 were analyzed. The analysis reveals that while the CIPP model is effective in evaluating program design and implementation, significant gaps remain, particularly regarding input factors such as teacher competence and resource availability. The review also highlights implementation limitations, emphasizing the urgent need for contextually adapted strategies, especially in rural and mountainous areas, to address inequities and promote sustainable literacy development. The limitation of this study lies in its restricted scope, which may not encompass all literacy initiatives across Indonesia. Based on these findings, it is recommended to strengthen teacher training, involve community stakeholders, and implement long-term monitoring to comprehensively improve literacy outcomes. Context-sensitive implementation and equitable resource allocation are also crucial.